Analysis of Engineering education in Brazil: a case study in the Midwest region (Research, Society and Development, 2020)
Higher education courses in the area of engineering have increased in recent decades in the Midwest region of Brazil. As a result, it is necessary to investigate the quality of education provided in this area, which directly influences the Brazilian economy. The objective of this work is to present an overview, in the students' view, on the didactic aspects and the use of methodologies of teachers in engineering courses in the Midwest region of Brazil. The methodology used was an online survey made available to students of engineering courses in that region. As a result, some inefficiencies and qualities of teaching practiced in engineering courses in this region can be traced. It is concluded that students still feel the need for evolution on the part of teachers and also the educational system, to optimize the teaching of engineering in the Midwest region.